Thermo-activated peroxydisulfate oxidation of indomethacin: Kinetics study and influences of co-existing substances. (December 2018) - Li, Ruobai; Cai, Meixuan; Liu, Haijin; Liu, Guoguang; Lv, Wenying
Abstract: The widespread occurrence of non-steroidal anti-inflammatory drugs (NSAIDs) (e.g., Indomethacin) in the ambient environment has attracted growing concerns due to their potential threats to ecosystems and human health. Herein, we investigated the degradation of indomethacin (IM) by thermo-activated peroxydisulfate (PDS). The pseudo first-order rate constant (kobs ) of degradation of IM was increased significantly with higher temperatures and PDS doses. Moreover, when the initial pH value was raised from 5 to 9 the IM degradation was initially decreased and then increased. Basic conditions were favorable for the removal of IM in the thermo-activated peroxydisulfate system. A response surface methodology based on the Box-Behnken design (BBD) was successfully employed for the optimization of the thermo-activated peroxydisulfate (PDS) system. The presence of chlorine ions manifested a dual effect on the degradation of IM, while bicarbonate and SRFA (as a NOM model) reduced it. Radical scavenging tests and electron spin resonance (ESR) revealed that the dominant oxidizing species were SO4 − and OH at pH 9. Furthermore, the TOC removal efficiency attained 28.8% and the release of Cl − was 38.5% at 60 °C within 24min, while the mineralization rate of IM were 85.5% with the PDS concentration up to 20  mM at 2 h oxidation. To summarize, thermo-activated PDS oxidation is a promising technique for the remediation of IM-contaminated water. Graphical abstract: Highlights: Indomethacin can be effectively degraded in thermo-activated peroxydisulfate system. A response surface methodology based on the Box-Behnken design (BBD) was successfully employed for the optimization of Indomethacin oxidation. Quenching studies and the ESR technique were both employed to identify radical species. The TOC removal efficiency and dechlorination of Indomethacin were determined.